Improving Stress and Positive Mental Health at Work via an App-Based Intervention: A Large-Scale Multi-Center Randomized Control Trial - Weber, Silvana; Lorenz, Christopher; Hemmings, Nicola (Frontiers in Psychology, 2019)
Mobile health interventions (i.e., ‘apps)’ are used to address mental health and are an increasingly popular method available to both individuals and organisations to manage workplace stress. However, at present, there is a lack of research on the effectiveness of mobile health interventions in counteracting or improving stress-related health problems, particularly in naturalistic, non-clinical settings. This project aimed at validating a mobile health intervention (which is theoretically grounded in the Job Demands-Resources Model) in preventing and managing stress at work. Within the mobile health intervention, employees make an evidence-based, personalised, psycho-educational journey to build further resources, and thus, reduce stress. A large-scale longitudinal randomised control trial, conducted with six European companies over six weeks using four measurement points, examined indicators of mental health via measures of stress, wellbeing, resilience, and sleep. The data were analysed by means of hierarchical multilevel models for repeated measures, including both self-report measures and user behaviour metrics from the app. The results (n = 532) suggest that using the mobile health intervention (vs. waitlist control group) significantly improved stress and wellbeing over time. Higher engagement in the intervention increased the beneficial effects. Additionally, use of the sleep tracking function led to an improvement in sleeping troubles. The intervention had no effects on measures of physical health or social community at work. Theoretical and practical implications of these findings are discussed, focusing on benefits and challenges of using technological solutions for organisations to support individuals’ mental health in the workplace.